Respuesta :

Perfect square trinomial

[tex] \boxed{ a^2 \pm 2ab+b^2 = (a \pm b)^2 } [/tex]

Using the perfect square trinomial

[tex] p^2 - 4p + 4 = 0 [/tex]

[tex] p^2 - 2(2p) + (2)^2 = 0 [/tex]

[tex] (p-2)^2 = 0 [/tex]

[tex] (p-2) = 0 [/tex]

[tex] p = 2 [/tex]

[tex]\huge\text{Hey there!}[/tex]

[tex]\bold{p^2-4p+4=0}[/tex]

[tex]\text{FACTOR the LEFT side of your equation}\\\bold{(p-2)(p-2)=0}[/tex]

[tex]\text{SET each of your FACTORS TO EQUAL to 0}\\\bold{p-2=0\ or\ p-2=0}[/tex]

[tex]\text{SIMPLIFY the equations\ above and you will have your answer}[/tex]

[tex]\boxed{\boxed{\bold{Answer: \large\text{\bf{p = 2}}}}}\huge\checkmark[/tex]

[tex]\textsf{Good luck on your assignment and enjoy your day!}[/tex]

~[tex]\frak{Amphitrite1040:)}[/tex]